Structure and function of the lysine methyltransferase SETD2 in cancer: From histones to cytoskeleton - Christina Michail; Fernando Rodrigues Lima; Mireille Viguier; Frédérique Deshayes (Neoplasia: An International Journal for Oncology Research)
SETD2 is known to be the unique histone methyltransferase responsible for the trimethylation of the lysine 36 of histone H3 thus generating H3K36me3. This epigenetic mark is critical for transcriptional activation and elongation, DNA repair, mRNA splicing, and DNA methylation. Recurrent SETD2-inactivating mutations and altered H3K36me3 levels are found in cancer at high frequency and numerous studies indicate that SETD2 acts as a tumor suppressor. Recently, SETD2 was further shown to methylate non-histone proteins particularly the cytoskeletal proteins tubulin and actin with subsequent impacts on cytoskeleton structure, mitosis and cell migration.Herein, we provide a review of the role of SETD2 in different cancers with special emphasis on the structural basis of the functions of this key lysine methyltransferase. Moreover, beyond the role of this enzyme in epigenetics and H3K36me3-dependent processes, we highlight the putative role of ''non-epigenetic/H3K36me3'' functions of SETD2 in cancer, particularly those involving the cytoskeleton.